Novel CRF1-receptor Antagonists from Pulsatilla koreana Root - Li, Wei; Noh, Hyojin; Lee, Sunghou; Lee, Min Ho; Lee, Eun Young; Kang, Sangjin; Kim, Young Ho (Natural product sciences, 2014)
In this study, twenty-one oleanane-type triterpenoid saponins were isolated from a methanol extract of the roots of Pulsatilla koreana. Antagonistic activities were measured in these compounds by the aequorin based cellular functional assay system for the corticotropin releasing factor receptor (CRF1). Of them, compounds 7 - 10 showed the highest degree of CRF1 inhibition further at the concentration of $10μM$. Moreover, by the analysis based on the structure-activity relationship of isolated saponins, a sugar chain at C-3 and a carboxyl group at C-28, as well as a methyl group at C-23 seems to be key functional elements. To our knowledge, this is the first report on CRF1 inhibition of saponins from P. koreana.